2013
DOI: 10.7314/apjcp.2013.14.12.7483
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus (HPV) Infection in Women Participating in Cervical Cancer Screening from 2006 to 2010 in Shenzhen City, South China

Abstract: The prevalence of HPV 18 infection is increasing faster than any others, which will lead it to be one of the main subtypes in this city in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…The strength of this study was that the age for participants covered from 18-81 years. Generally, the vast majority of the HPV prevalence was 19.76% in total participants and was higher than 13.8% of a hospital-based study in Shenzhen near to Shantou (Wang et al, 2013). For age-specific distribution, a higher prevalence of HPV infection was observed in both young (18-25 years) and old (> 65 years) age groups in the general population, in agreement with the previous report in Hunan population, mid-south China .…”
Section: Discussionsupporting
confidence: 88%
“…The strength of this study was that the age for participants covered from 18-81 years. Generally, the vast majority of the HPV prevalence was 19.76% in total participants and was higher than 13.8% of a hospital-based study in Shenzhen near to Shantou (Wang et al, 2013). For age-specific distribution, a higher prevalence of HPV infection was observed in both young (18-25 years) and old (> 65 years) age groups in the general population, in agreement with the previous report in Hunan population, mid-south China .…”
Section: Discussionsupporting
confidence: 88%
“…A high rate of HPV-DNA infection (44.4%) was observed in specimens taken from patients ranged from 17 to 79 years, and 35.1% was the HR-HPV types. The prevalence of HPV infection among females attending the cervical cancer screening varies in different regions of China, for example, in Shenzhen city, 13.8% of the volunteers was HPV positive; in Shanghai city, southeast of China, the infection rate was 30.2% (Xue et al, 2009;Wang et al, 2013). In the present study, the prevalence of HPV infection showed a significant difference among patients in the age groups (χ 2 =22.279, p<0.05).…”
Section: Discussionmentioning
confidence: 40%
“…Our findings showed the most prevalent HPV genotype was HPV 16 (9.2%, 53/578), followed by HPV 52 (7.8%, 45/578), HPV 6 (6.9%, 40/578), HPV 11 (5.9%, 34/578), HPV 42 (5.0%, 29/578) and HPV 58 (3.8%, 22/578), which was similar to that of Beijing city (Hou et al, 2012). In other regions of China, for example, in Zhejiang province, a coastal region in southeast China, the most predominant type was HPV 52 (3.1%), followed by HPV 16 (2.5%), HPV 58 (2.1%), HPV 68 (1.0%) and HPV 81 (0.9%) (Ye et al, 2010); in Shenzhen city, the five most commonly found HPV types were HPV 16 (3.47%), HPV 58 (1.68%), HPV 33 (1.38%), HPV 43 (1.36%) and HPV 18 (1.27%) (Wang et al, 2013). The difference may be due to the geographical and biological interplay between HPV types or variants and host immunogenic factors (Xue et al, 2009).…”
Section: Xiao-chuan Wang Et Almentioning
confidence: 98%
See 2 more Smart Citations